New players in the preventive treatment of migraine. Issue 1 (December 2015) - Mitsikostas, Dimos; Rapoport, Alan
Abstract Migraine is a common, chronic disorder of the brain causing much disability, as well as personal, familial and societal impact. Several oral preventive agents are available in different countries for the prevention of migraine, but none have performed better than 50 % improvement in 50 % of patients in a clinical trial. Additionally, each has various possible adverse events making their tolerability less than optimal. Recently, three monoclonal antibodies targeting the calcitonin gene-related peptide (CGRP) ligand (LY2951742, ALD403 and TEV-48125) and one targeting the CGRP receptor (AMG 334) have completed phase 2 trials, and the results have been reported. These early results show them all to be somewhat more effective than placebo, with no serious adverse events. Three have been studied for episodic migraine, and only TEV-48125 has been studied for both high frequency episodic and chronic migraine. Moreover, preliminary data suggests that neurostimulation is effective in migraine treatment, including stimulation of the sphenopalatine ganglion, transcutaneous supraorbital and supratrochlear nerve, and transcutaneous vagus nerve. In this article, these innovative therapies will be reviewed.